PENGGUNAAN LARUTAN KANJI PADA PENYIMPANAN BUAH SAWO (Achras zapota L.) - Titin Rahmattiah; Eko Basuki; Agustono Prarudiyanto (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2017)
This study aims to determine the use of the starch solution on storage of sapodilla fruit (Acharas zapota l.). Completely Randomized Design (CRD) is used with the factors of starch solution 0%, 1%, 2%, 3% and 4%. The parameters are observed in the chemical properties include moisture, reducing sugar, total dissolved solids, physical properties include weight loss, texture and organoleptic (taste and flavor). The results were significantly different analysis further tested using orthogonal polynomial contrast to chemical parameters while organoleptic test parameters tested with Honestly Significant Difference (HSD). These results indicates that administration of starch solution provides real effect on water content and not significant towards reducing sugar, total weight less, texture and test organoleptic (taste and Flavor). Provision of 2% starch solution in reducing sugar gives the lowest value on day 7 and day 14. Lowest texture value contained in the administration of starch solution 4% on day 7 and day 14, while for the highest value contained at a concentration of 2% on the storage day 7 and day 14. Organoleptic test of the quality of taste after storage provides the highest value consumer preferences with concentration of 1% with a storage time of 7 days. Keywords: sapodilla fruit, starch solution, storage ABSTRAK Penelitian ini bertujuan untuk mengetahui penggunaan larutan kanji pada penyimpanan buah sawo (Acharas zapota l.).Rancangan percobaan yang digunakan yaitu rancangan acak lengkap (RAL) satu faktor (penggunaan larutan kanji 0%, 1%, 2%, 3% dan 4%). Parameter yang diamati adalah sifat kimia (kadar air, gula reduksi, total padatan terlarut), sifat fisik (susut berat, tekstur) dan uji organoleptik. Hasil analisa yang berbeda nyata diuji lanjut menggunakan kontras orthogonal polynomial untuk parameter kimia sedangkan untuk parameter uji organoleptik diuji dengan beda nyata jujur (BNJ). Hasil penelitian menunjukkan bahwa pemberian larutan kanji tidak memberikan pengaruh nyata terhadap semua parameter kecuali kadar air. Pemberian larutan kanji 2% pada gula reduksi memberikan nilai terendah pada hari ke-7 dan hari ke-14. Nilai tekstur terendah terdapat pada pemberian larutan kanji 4% pada hari ke-7 dan hari ke-14 sedangkan untuk nilai tertinggi terdapat pada konsentrasi 2% pada penyimpanan hari ke-7 dan hari ke-14. Uji organoleptik terhadap mutu rasa setelah penyimpanan memberikan nilai kesukaan konsumen paling tinggi dengan konsentrasi larutan kaji 1% dengan lama penyimpanan 7 hari. Kata kunci: buah sawo,larutan kanji, penyimpanan